Reduced efficacy of baiting programs for invasive species: Some mechanisms and management implications - Allsop, S.; Dundas, S.; Adams, P.; Kreplins, T.; Bateman, Bill; Fleming, P. (Surrey Beatty and Sons, 2017)
'Bait-resistance' is defined as progressive decreases in bait efficacy in controlled pest species populations. Understanding the mechanisms by which bait-resistance can develop is important for the sustainable control of pests worldwide, for both wildlife conservation programs and agricultural production. Bait-resistance is influenced by both behavioural (innate and learned bait-avoidance behaviour) and physiological aspects of the target pest species (its natural diet, its body mass, the mode of action of the toxin, and the animal's ability to biochemically break down the toxin). In this review, we summarise the scientific literature, discuss factors that can lead to innate and learned aversion to baits, as well as physiological tolerance. We address the question of whether bait avoidance or tolerance to 1080 could develop in the red fox (Vulpes vulpes), an introduced predator of significant economic and environmental importance in Australia. Sublethal poisoning has been identified as the primary cause of both bait avoidance and increased toxin-tolerance, and so, finally, we provide examples of how management actions can minimise the risk of sublethal baits in pest species populations.